THE NECESSITY TO REFORM INDONESIAN LEGAL FRAMEWORK ON PROVISIONAL ARRANGEMENT TO COMBAT IUU FISHING - Husein, Yunus; Aziz, Muhammad Faiz (UI Scholars Hub, 2020)
Indonesia has not yet concluded its maritime boundaries with neighbouring countries. Incidents often occur including Illegal Unreported and Unregulated Fishing (IUU) Fishing conducted by fishers from neighboring countries. In fact, their actions are sometimes backed by their /coast guard. Maritime delimitation is the final goal that must be achieved to provide legal certainty over the territory and Exclusive Economic Zone of Indonesia and its neighbours. However, achieving that goal is never been easy. Article 74(3) of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 determines joint or provisional arrangements between disputing countries as temporary solution before reaching agreement on delimitation in EEZ. Indonesia must utilize and optimize this provision in order to combat the IUU Fishing, to protect fisheries resources and to support in achieving maritime boundary delimitation. The state already has the relevant legal and institutional framework to implement the provisional arrangement and, once, had a provisional arrangement with Australia decades ago although in the field of hydrocarbon. The arrangement was deemed as the most prominent one at that time. The experience of other countries in implementing of provisional arrangement in combating IIU Fishing, protecting the resources and achieving maritime delimitation might encourage Indonesia to utilize and optimize provisional arrangements in disputed areas.